Penerapan Strategi Pembelajaran Word Square Pada Mata Pelajaran Fikih Kelas X di MAS Al-Manaar Batuhampar - Mahfuzoh Mahfuzoh; Nurhasnah Nurhasnah; Wedra Aprison; Jasmienti Jasmienti (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This research was motivated by a fiqh subject teacher who applied the Word Square learning strategy in the learning process he carried out, learning was still teacher-centered so that interactions between students and teachers rarely occurred, students were less thorough in finding answers to the problems given, there were still students who are less able to work in discussion groups and solve problems, and students tend to study individually. This research aims to find out: How the Word Square learning strategy is implemented in the class X jurisprudence subject at MAS Al-Manaar Batuhampar and the obstacles teachers face in implementing the Word Square learning strategy in the class This research uses a type of field research using descriptive methods. The descriptive method can be interpreted as a way of solving the problem being investigated by describing the research object based on visible facts or as they really are. Data collected through observation, interview and documentation methods. Based on the research results, it can be concluded that the implementation of the Word Square learning strategy carried out by the class X fiqh teacher at MAS Al-Manaar Batuhampar has been implemented well through appropriate procedures or steps. The steps in implementing the Word Square learning strategy consist of, firstly, an opening activity which is carried out by opening the lesson with greetings, providing motivation and dividing into discussion groups. The two core activities are carried out by delivering material, distributing Word Square worksheets, giving direction to group work and discussing assignments. The three final activities were carried out by providing enriching material and closing the learning with greetings. In implementing the Word Square learning strategy, the fiqh subject teacher also found several obstacles, namely, students who were less active, lack of student discipline and lack of mutual respect between group members.